2007
DOI: 10.1021/jm0613323
|View full text |Cite
|
Sign up to set email alerts
|

An Adamantyl-Substituted Retinoid-Derived Molecule That Inhibits Cancer Cell Growth and Angiogenesis by Inducing Apoptosis and Binds to Small Heterodimer Partner Nuclear Receptor:  Effects of Modifying Its Carboxylate Group on Apoptosis, Proliferation, and Protein-Tyrosine Phosphatase Activity

Abstract: Apoptotic and antiproliferative activities of small heterodimer partner (SHP) nuclear receptor ligand (E)-4-[3'-(1-adamantyl)-4'-hydroxyphenyl]-3-chlorocinnamic acid (3-Cl-AHPC), which was derived from 6-[3'-(1-adamantyl)-4'-hydroxyphenyl]-2-naphthalenecarboxylic acid (AHPN), and several carboxyl isosteric or hydrogen bond-accepting analogues were examined. 3-Cl-AHPC continued to be the most effective apoptotic agent, whereas tetrazole, thiazolidine-2,4-dione, methyldinitrile, hydroxamic acid, boronic acid, 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 77 publications
1
33
0
2
Order By: Relevance
“…The incorporation of an adamantyl moiety into various molecules resulted in compounds with relatively high lipophilicity, which could modify or improve the biological availability [9]. It has been reported that retinoid compounds substituted with adamantyl showed a proapoptotic and antiangiogenesis activity in solid tumors, with an improved pharmacological profile [10]. In addition, the adamantylbased 1,4-hydroquinone was reported as potent tyrosine kinase inhibitor, which was 3-fold more potent at inducing the downregulation of the chronic myelogenous leukemia-specific tyrosine kinase (p210 bcr/abl ) [11].…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of an adamantyl moiety into various molecules resulted in compounds with relatively high lipophilicity, which could modify or improve the biological availability [9]. It has been reported that retinoid compounds substituted with adamantyl showed a proapoptotic and antiangiogenesis activity in solid tumors, with an improved pharmacological profile [10]. In addition, the adamantylbased 1,4-hydroquinone was reported as potent tyrosine kinase inhibitor, which was 3-fold more potent at inducing the downregulation of the chronic myelogenous leukemia-specific tyrosine kinase (p210 bcr/abl ) [11].…”
Section: Introductionmentioning
confidence: 99%
“…It was recognized that dysfunction of the apoptosis machinery was a hallmark of cancer [12][13][14], and induction of apoptosis was arguably the most potent defense against cancer [5]. Therefore, much attention was paid to the design and discovery of apoptotic inducers during recent years [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], and promising results have been obtained in this way. Compounds 2 [5] and 3 [34] were the representative reported apoptotic inducers (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the combination of these studies gives rise to an intriguing scenario where small molecules oppositely regulate SHP functions. In line with these observations, further studies by Dawson and coworkers reported the importance of the carboxylic moiety of 1 and 2 for the apoptotic activity and, more recently, an interaction model of these compounds at the proposed ligand binding site of SHP has been suggested, though pending for further experimental appraisals [31, 32]. …”
Section: Introductionmentioning
confidence: 76%